Students’ perception and achievement on online English learning platforms - Rachmat Ari Wibowo; Davis Wright Charlotte (Journal of Research in English Language Teaching and Linguistics, 2025)
This study explores students' perceptions and academic achievements in online English learning platforms, a topic of increasing importance due to the global shift towards digital education. Existing research has extensively examined technical features, pedagogical strategies, and learner motivation in virtual language learning environments. However, a significant gap remains in understanding how students' subjective experiences align with their measurable performance outcomes within these platforms. The primary aim of this research is to investigate how students perceive their online English learning experiences and how these perceptions relate to their academic achievements. To achieve this, the study employed a qualitative research design involving 19 university students from Indonesia, selected through purposive sampling. Data collection involved individual interviews conducted online via video conferencing, lasting between 30 to 45 minutes, and was supplemented by academic achievement data sourced from institutional records. Data analysis was performed through thematic analysis, involving multiple readings of transcripts, coding, and categorization of emerging themes related to perceived benefits and challenges of online platforms. The findings reveal that students appreciated the flexibility and multimedia features of online platforms, which supported autonomous learning, yet faced challenges such as limited interaction, technical issues, and self-discipline demands. Notably, students' perceptions were positively correlated with academic performance; those with higher self-regulation skills and positive attitudes toward digital tools tended to perform better academically. The study highlights the necessity for holistic platform design and pedagogical strategies that foster interaction, emotional support, and learner autonomy. The implications suggest that educators, developers, and policymakers should consider both technological and human factors to optimize online language learning experiences, ultimately enhancing learner engagement and achievement in digital environments.